Silase Jagung, Rumput Gajah dan Pucuk Tebu dalam Ransum Sapi Perah Jantan - T. Sutardi (Buletin Ilmu Makanan Ternak, 1990)
Napier grass, either as sole forage or in a 50:50 combination with sugarcane tops was evaluated and compared with corn silage in growing dairy bulls. Twenty one bulls, 14.0 0.81 month of age, averaging 377  30kg in weight, were divided into weight groups. They were then fed with isocaloric and isonitrogenous diets containing either 50% corn silage, 35% Napier grass or 35% Napier grass + sugarcane tops gained 0.930 kg daily. This was significantly lower (P<0.05) than those on corn silage (1.0290 kg) or Napier grass (0.973 kg). They also consumed less dry matter (9.200 vs 9.886 and 9.929 kg) suggesting that the lower growth performance mainly due the lower palatability of the sugarcane diet. However, partial substitution of Napier grass with sugarcane tops reduced feed/gain (Rp. 1.283.02 vs Rp. 1.075.61). Eventhough corn silage was expensive (Rp. 42.--/kg vs Rp. 18.--/kg Napier grass and Rp. 14.--/kg sugarcane tops), feed cost/gain of the corn silage diet was still the cheapest (Rp. 959.24).